Low-impedance thick electrode and lithium ion battery applying same

By setting an electrolyte layer in the thick electrode, the problem of large ion transport impedance in the thick electrode is solved, and the dynamic performance and cycling stability of the lithium battery are improved.

CN222619770UActive Publication Date: 2025-03-14EVE POWER CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202420856021.2
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2024-04-23
Publication Date
2025-03-14
Estimated Expiration
2034-04-23

AI Technical Summary

Technical Problem

The large ion transport impedance in the thick electrode limits the dynamic performance of the lithium battery and has poor mechanical stability, resulting in deterioration of rate performance and cycling performance.

Method used

An electrolyte layer is provided between the first active coating and the second active coating. The electrolyte layer is composed of a polymer film skeleton and an electrolyte, which has high ionic conductivity and good interface compatibility, which promotes charge transport and improves the wetting properties of the electrolyte.

Benefits of technology

The charge exchange impedance of low-impedance thick electrodes is reduced, and the rate performance, high-temperature storage performance and cycling performance of lithium-ion batteries are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222619770U_ABST
    Figure CN222619770U_ABST
Patent Text Reader

Abstract

The utility model provides a low impedance thick electrode, which comprises a current collector, a first active coating, an electrolyte layer and a second active coating which are sequentially arranged, the first active coating and the second active coating are connected through the electrolyte layer, and electrolyte is arranged in the electrolyte layer. The low-impedance thick electrode is low in ion diffusion impedance in the pole piece, high in lithium ion transmission efficiency and good in electrolyte wettability in the pole piece.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model belongs to the technical field of batteries, and in particular relates to a low-impedance thick electrode and a lithium-ion battery using the same. Background Art

[0002] Without changing the battery chemistry, the thick electrode structure increases the content of active materials per unit volume of the battery, reduces the amount of current collector used, and increases the energy density of the battery system. Therefore, improving the energy density of batteries through thick electrode structure design has received widespread attention.

[0003] However, the slow transfer of ions and electrons inside thick electrodes and poor mechanical stability lead to deterioration of their rate capability and cycle performance. There are four main factors affecting charge transfer in thick electrodes: (1) lithium ion transfer in the electrolyte; (2) charge transfer at the interface between the electrolyte and the electrode; (3) diffusion of lithium ions inside the electrode; and (4) charge transfer at the interface between the current collector and the electrode. Therefore, the impedance in thick electrodes can be divided into: electronic impedance, charge transfer impedance, bulk impedance of the electrolyte, and ion transfer impedance in the electrode. A large number of studies have shown that the ion transfer impedance in thick electrodes is the main factor limiting the kinetic performance of thick electrode lithium batteries.

[0004] The main reason for the high ion transfer impedance of thick electrodes is the long lithium ion transfer channel and poor electrolyte wettability inside the electrode. Therefore, it is necessary to explore a thick electrode with fast lithium ion transfer efficiency and good electrolyte wettability inside the electrode. Utility Model Content

[0005] In view of the shortcomings of the prior art, the purpose of the utility model is to provide a low-impedance thick electrode, which has low ion diffusion impedance inside the electrode piece, high lithium ion transmission efficiency and good electrolyte wettability inside the electrode piece.

[0006] According to one aspect of the utility model, a low-impedance thick electrode is provided, comprising a current collector, a first active coating, an electrolyte layer, and a second active coating arranged in sequence, wherein the first active coating and the second active coating are connected via the electrolyte layer, and an electrolyte is provided in the electrolyte layer.

[0007] Compared with conventional thick electrodes, this solution sets an electrolyte layer between the first active coating and the second active coating, so that the internal ion diffusion impedance of the pole piece of the low-impedance thick electrode with this structure is lower, so during the operation of the battery, the ion diffusion rate in the pole piece is faster. The electrolyte layer has high ionic conductivity and good interface compatibility, which can promote the transfer of charges in the second active coating to the first active coating, reduce the charge difference between the first active coating and the second active coating, and thus reduce the charge exchange impedance. Secondly, the electrolyte layer can also improve the wettability of the electrolyte to the low-impedance thick electrode, thereby improving the battery's rate performance, high-temperature storage performance and cycle performance.

[0008] Preferably, the electrolyte layer includes a polymer membrane skeleton, and the electrolyte is loaded on the polymer membrane skeleton. The polymer membrane skeleton can restrain the loss of electrolyte, so that the low-impedance thick electrode is not easy to lose electrolyte during battery storage. Furthermore, the load in the electrolyte layer is equivalent to a high-speed transmission channel for ions and electrons, which can reduce the diffusion resistance of lithium ions, thereby slowing down the cycle capacity decay.

[0009] Preferably, the electrolyte layer is composed of a gel polymer electrolyte (GPE). Such a gel polymer electrolyte includes a polymer membrane skeleton and an electrolyte loaded in the polymer membrane skeleton. Compared with inorganic solid electrolytes, gel polymer electrolytes have better flexibility. Therefore, using gel polymer electrolytes as electrolyte layers can also improve the structural stability of the low-impedance thick electrode. When winding and bending electrodes or laminations to prepare batteries, the electrodes are not easy to fall off or break; during the operation of the battery, it can also buffer the volume expansion of the active material, further improve the structural stability of the low-impedance thick electrode, and thus improve the cycle stability of the battery. Commonly used gel polymer electrolytes include PEO-based gel polymer electrolytes, PMMA-based gel polymer electrolytes, PAN-based gel polymer electrolytes, PVDF-HFP-based gel polymer electrolytes, and bio-based gel polymer electrolytes.

[0010] Preferably, the electrolyte layer has a microporous structure, the porosity of the electrolyte layer is 55% to 58%, and the average pore size of the micropores is 0.5 μm to 1 μm. The micropores in the electrolyte layer can provide more paths for the electrolyte to infiltrate the electrodes, which is beneficial to reduce the ion transmission resistance inside the electrodes, thereby reducing the internal resistance of the electrodes, improving the conductivity of the electrodes, accelerating the migration speed of electrons in the lithium battery, and further improving the working performance of the lithium-ion battery.

[0011] Preferably, the polymer film skeleton is composed of a polymer selected from one of polyethylene oxide, polymethyl methacrylate, polyacrylonitrile, polyvinylidene fluoride, and (polyvinylidene fluoride-hexafluoropropylene) copolymer. When a support structure that meets the above conditions is used, the mechanical properties of the low-impedance thick electrode can be further improved, so that the battery using the low-impedance thick electrode has good cycle stability.

[0012] Preferably, the polymer is polyvinylidene fluoride. Through experiments and tests by the inventors, it is found that when the polymer includes polyvinylidene fluoride PVDF, the high temperature resistance of the low-impedance thick electrode can be further improved, and the high temperature storage performance of the battery using the low-impedance thick electrode can be improved. Even if the battery has been stored at high temperature for a long time, its discharge capacity can be easily restored to the discharge capacity of the battery at room temperature.

[0013] Preferably, in the thickness of the low-impedance thick electrode, the thickness of the electrolyte layer accounts for 6.7% to 8.9%. When the thickness of the electrolyte layer accounts for a proportion within the above range, the electrolyte layer has a better improvement effect on the low-impedance thick electrode, and can balance the low ion impedance, high ion transport performance, high electrolyte wettability and structural stability of the low-impedance thick electrode. If the thickness of the electrolyte layer accounts for too large a proportion, the thickness of the first active coating and the second active coating in the electrode piece accounts for too small a proportion, that is, the proportion of the active material is too small, which easily reduces the energy density of the electrode; if the thickness of the electrolyte layer accounts for too small a proportion, the improvement effect of the electrolyte layer on the electrode in reducing impedance and improving electrolyte wettability is not obvious enough.

[0014] Preferably, the thickness of the electrolyte layer is 6 to 8 μm. When the thickness of the electrolyte layer falls within the above range, the electrolyte layer has a more significant improvement effect on the low-impedance thick electrode, and can better balance the charge transfer impedance and energy density of the electrode sheet.

[0015] Preferably, the thickness of the first active coating: the thickness of the second active coating = 4.5-5.5: 4.5-5.5. When the thickness of the first active coating and the second active coating meet the above ratio, the electrolyte layer between the first active coating and the second active coating can better play the role of improving the electrolyte wettability and better balance the electrolyte wettability of the first active coating and the second active coating. If the thickness ratio of the first active coating to the second active coating is too small, it is equivalent to the first active coating being too thick. At this time, the electrolyte cannot well infiltrate the first active coating, resulting in the electrolyte being difficult to penetrate into the electrolyte layer, and then difficult to penetrate into the second active coating. If the thickness ratio of the first active coating to the second active coating is too large, it is equivalent to the second active coating being too thick. At this time, although the electrolyte can well infiltrate the first active coating and the electrolyte layer, due to the thick second active coating, it is still difficult to completely infiltrate the second active coating.

[0016] Preferably, the thickness of the first active coating layer: the thickness of the second active coating layer=5:5.

[0017] Preferably, the thickness of the first active coating is 41-42 μm; the thickness of the second active coating is 41-42 μm. When the thickness of the first active coating and the second active coating meet the above range, the low-impedance thick electrode has high energy density and low ion transfer impedance.

[0018] According to another aspect of the utility model, a lithium ion battery is provided, comprising the low impedance thick electrode. The low impedance thick electrode can be used as the positive electrode and / or negative electrode of the lithium ion battery, and the lithium ion battery using the low impedance thick electrode has low charge transfer impedance, low solid phase transfer impedance, high cycle stability, and high capacity retention rate.

[0019] Preferably, the negative electrode of the lithium-ion battery is a low-impedance thick electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 A schematic diagram of the structure of a low-impedance thick electrode provided in Example 1;

[0021] Figure 2 A schematic diagram of the structure of a thick electrode provided for Comparative Example 1;

[0022] Figure 3 A schematic diagram of the structure of a thick electrode provided for Comparative Example 2;

[0023] Figure 4 A schematic diagram of the structure of a thick electrode provided for Comparative Example 3;

[0024] Figure 5 The electrochemical impedance spectra of the batteries in Example 1 and Comparative Example 1 are measured;

[0025] The meanings of the reference numerals are as follows:

[0026] 1. Second active coating; 2. Electrolyte layer; 3. First active coating; 4. Current collector; 5. Third active coating. DETAILED DESCRIPTION

[0027] For better understanding and implementation, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0028] In the description of the present invention, it should be noted that the terms "upper", "lower", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside" and "outside" etc. indicating directions or positional relationships are based on the directions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific direction, be constructed and operated in a specific direction, and therefore cannot be understood as a limitation on the present invention.

[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0030] Example 1

[0031] The utility model provides a low-impedance thick electrode, the structure of which is as follows Figure 1 shown.

[0032] The low-impedance thick electrode comprises a current collector 4, a first active coating 3, an electrolyte layer 2, and a second active coating 1 which are composited in sequence. The electrolyte layer 2 comprises a polymer membrane skeleton (not shown in the figure) and an electrolyte (not shown in the figure), and the electrolyte is loaded on the polymer membrane skeleton. The first active coating 3 and the second active coating 1 are connected through the electrolyte layer. Among them, the electrolyte layer 2 plays a role in reducing the charge difference between the first active coating 3 and the second active coating 1, thereby reducing the charge exchange impedance of the low-impedance thick electrode.

[0033] Furthermore, the electrolyte layer 2 is composed of a gel polymer electrolyte including a polymer membrane skeleton and an electrolyte. Specifically, the polymer skeleton is composed of a polymer, the polymer is polyvinylidene fluoride, and the electrolyte is a LiPF6 electrolyte. Specifically, the electrolyte layer 2 can also improve the wettability of the electrolyte to the low-impedance thick electrode. The load is equivalent to a high-speed transmission channel for ions and electrons in the low-impedance thick electrode, which can reduce the diffusion resistance of lithium ions, thereby slowing down the cycle capacity decay. The support structure can restrain the loss of the electrolyte and improve the structural stability of the low-impedance thick electrode.

[0034] Furthermore, the electrolyte layer 2 has a microporous structure, so that the porosity of the electrolyte layer 2 is 57%, and the average pore size of the micropores is 0.8 μm. Specifically, the micropores in the electrolyte layer 2 can provide more paths for the electrolyte to infiltrate the electrode, which is conducive to reducing the ion transmission resistance inside the electrode.

[0035] In other embodiments, the material composition type and microporous structure of the electrolyte layer 2 can be adjusted according to different battery requirements, such as the polymer membrane skeleton of the electrolyte layer 2, the type of electrolyte and the porosity of the electrolyte layer 2, and the average pore size of the micropores, provided that the normal use of the low-impedance thick electrode is not affected.

[0036] Further, the first active coating 3, the electrolyte layer 2, and the second active coating 1 together constitute an active layer, wherein the thickness of the current collector 4 is 6 μm, the thickness of the first active coating 3 is 41.5 μm, the thickness of the electrolyte layer 2 is 7 μm, and the thickness of the second active coating 1 is 41.5 μm. It is calculated that the thickness of the electrolyte layer 2 is 7.8% of the thickness of the active layer.

[0037] Furthermore, the current collector 4 is made of copper foil. The first active coating 3 includes an active material, which is graphite. The second active coating 1 includes an active material, which is graphite.

[0038] In other embodiments, the type of the current collector 4, the type of active material of the first active coating 3, the type of material of the load and the supporting structure in the electrolyte layer 2, the type of active material of the second active coating 1, and the thickness of the current collector 4, the first active coating 3, the electrolyte layer 2, and the second active coating 1 can be adjusted according to different battery requirements, provided that the normal use of the low-impedance thick electrode and the lithium-ion battery is not affected.

[0039] Example 2

[0040] This embodiment provides a low impedance thick electrode based on the embodiment 1. The difference between this embodiment and the embodiment 1 is that the material type of the gel polymer electrolyte constituting the electrolyte layer 2 is adjusted, specifically, a LiPF6 electrolyte of equal thickness is selected to replace the gel polymer electrolyte selected in the embodiment 1. The rest of the structure is strictly consistent with the embodiment 1.

[0041] Example 3

[0042] This embodiment provides a low impedance thick electrode based on the embodiment 1. The difference between this embodiment and the embodiment 1 is that the thickness of the electrolyte layer 2 is adjusted so that the thickness of the electrolyte layer 2 accounts for 8.9% of the thickness of the active layer. Specifically, the thickness of the electrolyte layer 2 is 8 μm. The rest of the structure is strictly consistent with the embodiment 1.

[0043] Example 4

[0044] This embodiment provides a low-impedance thick electrode based on the embodiment 1. The difference between this embodiment and the embodiment 1 is that the thickness of the electrolyte layer 2 is adjusted so that the thickness of the electrolyte layer 2 accounts for 6.7% of the thickness of the active layer. Specifically, the thickness of the electrolyte layer 2 is 6 μm. The rest of the structure is strictly consistent with the embodiment 1.

[0045] Comparative Example 1

[0046] This comparative example provides a thick electrode based on Example 1, and the specific structure is as follows: Figure 2 As shown. The difference between this comparative example and Example 1 is that the thick electrode provided in this comparative example includes a current collector 4 and a third active coating 5 which are compounded in sequence, the thickness of the third active coating 5 is consistent with the sum of the thicknesses of the first active coating 3 and the second active coating 1 in Example 1, and the raw material composition of the third active coating 5 is consistent with the raw material composition of the first active coating 3 and the second active coating 1 in Example 1. The rest of the structure, raw material composition, and thickness are strictly consistent with Example 1.

[0047] Comparative Example 2

[0048] This comparative example provides a thick electrode based on comparative example 1, and the specific structure is as follows Figure 3 The difference between this comparative example and comparative example 1 is that the thick electrode provided in this comparative example includes a current collector 4, an electrolyte layer 2, and a third active coating 5 which are composited in sequence. Specifically, the structure, raw material composition, and thickness of the electrolyte layer 2 are consistent with those of the electrolyte layer 2 in Example 1. The rest of the structure is strictly consistent with that in comparative example 1.

[0049] Comparative Example 3

[0050] This comparative example provides a thick electrode based on comparative example 1, and the specific structure is as follows Figure 4 The difference between this comparative example and comparative example 1 is that the thick electrode provided in this comparative example includes a current collector 4, a third active coating 5, and an electrolyte layer 2 which are composited in sequence. Specifically, the structure, raw material composition, and thickness of the electrolyte layer 2 are consistent with those of the electrolyte layer 2 in Example 1. The rest of the structure is strictly consistent with that in comparative example 1.

[0051] Test Example 1

[0052] Test objects: The low-impedance thick electrodes provided in Examples 1 to 4 and the thick electrodes provided in Comparative Examples 1 to 3 were used as negative electrode sheets, respectively assembled with positive electrode sheets, electrolytes, and separators into lithium-ion batteries, and the assembled lithium-ion batteries were used as test objects.

[0053] Test items:

[0054] (1) Initial efficiency and DC internal resistance DCR: Each test object was charged to 3.65 V at 0.33 C, left for 30 min, then adjusted to 50% SOC at 0.33 C, left for 10 min, and discharged at 1 C for 30 s. The voltage at the last second of the standby period was U1, and the voltage at the last second of the 1 C discharge was U2. The initial efficiency and DC internal resistance DCR of the battery were recorded by R = (U1-U2) / t.

[0055] (2) Discharge capacity retention rate: Each test object was charged to 3.65 V at 0.33 C and left for 30 min. The charge capacity was Q1. The battery was discharged to 2.5 V at 1 C and 2 C respectively. The discharge capacity was Q2. The 1 C discharge capacity retention rate and 2 C discharge capacity retention rate were calculated by Q2 / Q1.

[0056] (3) High-temperature storage recovery rate: Each test object was charged and discharged at 0.33C for 5 cycles at 25°C, and the average discharge capacity of the 5 cycles was taken as Q3. After charging to 3.65V at 0.33C, it was stored at a constant temperature of 45°C for 30 days, taken out, left at 25°C for 2h, and discharged to 2.5V at 0.33C. The discharge capacity was taken as Q4. The high-temperature storage recovery rate after storage at 45°C for 30 days was calculated by Q4 / Q3.

[0057] (4) Charge transfer impedance (Rct) and solid-phase transfer impedance (Rw): Each test object was fully charged (1C constant current and constant voltage charging to 3.65V), and the electrochemical impedance spectrum (EIS) of each test object was tested using a professional instrument, and the charge transfer impedance (Rct) and solid-phase transfer impedance (Rw) of each test object were recorded.

[0058] Test results: as shown in Table 1.

[0059] Table 1. Test performance of each test object

[0060]

[0061]

[0062] Result analysis:

[0063] By comparing the test performance of the lithium-ion batteries provided in Examples 1 to 4 with those in Comparative Examples 1 to 3, it can be found that, compared with Comparative Examples 1 to 3, the lithium-ion batteries using low-impedance thick electrodes in Examples 1 to 4 have better electrochemical performance, and have both excellent cycle capacity retention and high temperature resistance.

[0064] Among them, by comparing the test performance of Example 1 with that of Comparative Examples 1 to 3 in Table 1, it can be found that the initial efficiency and internal resistance of the lithium ion battery of Example 1 are lower than those of Comparative Examples 1 to 3, and the lithium ion battery of Example 1 has a cycle capacity retention rate and a high temperature capacity recovery rate higher than those of Comparative Examples 1 to 3. This shows that the electrolyte layer 2 is provided between the first active coating 3 and the second active coating 1, and the first active coating 3 and the second active coating 1 are connected through the electrolyte layer 2. The charge exchange impedance of the low-impedance thick electrode can be effectively reduced, thereby improving the electrochemical performance of the lithium ion battery.

[0065] Among them, the EIS curves of Example 1 and Comparative Example 1 are as follows: Figure 5 As shown, from Figure 5 It can be seen that compared with the lithium ion battery of Comparative Example 1, the lithium ion battery provided in Example 1 has smaller charge transfer impedance (Rct) and solid phase transfer impedance (Rw).

[0066] The above embodiments are only used to illustrate the technical solution of the utility model rather than to limit the protection scope of the utility model. Although the utility model is described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the utility model can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the utility model.

Claims

1. A low impedance thick electrode, characterized in that: The invention comprises a current collector, a first active coating, an electrolyte layer and a second active coating which are arranged in sequence. The first active coating and the second active coating are connected via the electrolyte layer, and an electrolyte is arranged in the electrolyte layer.

2. The low-impedance thick electrode according to claim 1, characterized in that: The electrolyte layer includes a polymer membrane skeleton, and the electrolyte is supported on the polymer membrane skeleton.

3. The low impedance thick electrode according to claim 1, characterized in that: The electrolyte layer has a microporous structure, the porosity of the electrolyte layer is 55% to 58%, and the average pore size of the micropores is 0.5 μm to 1 μm.

4. The low-impedance thick electrode according to claim 2, characterized in that: The polymer membrane skeleton is composed of a polymer, and the polymer is selected from one of polyethylene oxide, polymethyl methacrylate, polyacrylonitrile, polyvinylidene fluoride, and (polyvinylidene fluoride-hexafluoropropylene) copolymer.

5. The low impedance thick electrode according to claim 4, characterized in that: The polymer is polyvinylidene fluoride.

6. The low-impedance thick electrode according to any one of claims 1 to 5, characterized in that: The first active coating, the electrolyte layer and the second active coating together constitute an active layer. In the thickness of the active layer, the thickness of the electrolyte layer accounts for 6.7% to 8.9%.

7. The low impedance thick electrode according to claim 6, characterized in that: The thickness of the electrolyte layer is 6-8 μm.

8. The low impedance thick electrode according to claim 1, characterized in that: The thickness of the first active coating layer: the thickness of the second active coating layer = 4.5-5.5: 4.5-5.

5.

9. The low-impedance thick electrode according to claim 8, characterized in that: The thickness of the first active coating is 41-42 μm; the thickness of the second active coating is 41-42 μm.

10. A lithium ion battery, characterized in that: It comprises the low-impedance thick electrode as claimed in any one of claims 1 to 9.